2018
DOI: 10.1097/rli.0000000000000411
|View full text |Cite
|
Sign up to set email alerts
|

Non contrast, Pseudo-Continuous Arterial Spin Labeling and Accelerated 3-Dimensional Radial Acquisition Intracranial 3-Dimensional Magnetic Resonance Angiography for the Detection and Classification of Intracranial Arteriovenous Shunts

Abstract: Noncontrast PCASL-MRA with 3D radial acquisition is a potential tool for the detection and characterization of intracranial AV shunts with a sensitivity and specificity equivalent or higher than routine clinical MRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Concordance of the angioarchitectures of AVMs and AVFs between CS-TOF, PI-TOF, and DSA was calculated with unweighted and weighted kappa statistics [13,14,25]. Table 1 summarizes the patient characteristics of analysis 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concordance of the angioarchitectures of AVMs and AVFs between CS-TOF, PI-TOF, and DSA was calculated with unweighted and weighted kappa statistics [13,14,25]. Table 1 summarizes the patient characteristics of analysis 1.…”
Section: Discussionmentioning
confidence: 99%
“…This was in line with past studies showing TOF-MRA as a versatile tool for detecting AVS. Past studies have reported that clinical MRA including TOF-MRA was useful in the detection of AVS with 90-91.7% sensitivity and 94.4-100% specificity [25,27]. Regarding the fact that extracranial vessels, such as the occipital and middle meningeal arteries, often feed intracranial AVF, MRA of the whole brain at high resolution would be optimal for assessing AVF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,[22][23][24] Therefore, the entire scan-time usually needs to be spent for completing k-space, not for signal averaging as in perfusion imaging. The typical readout sequence used for ASL-MRA is based on gradient-echo sequences, such as turbo field-echo (TFE) 2,3 and spoiled gradient-echo (SPGR), [24][25][26][27] in which quite a number of excitation RF-pulses are applied. For dynamic MRA, the acquisition of multiple TIs/PLDs is generally performed using a Look-Locker readout, 28 in which the gradient-echo sequence is segmented into shorter shots with a duration equal to (or shorter than) the desired temporal resolution (typically 100-200 ms).…”
Section: Spatial Resolution and Readout Sequencementioning
confidence: 99%
“…[2][3][4][5] When imaging static 3D-MRA, however, the abovementioned dilemma is no longer relevant, and long pCASL labeling duration will ensures visualization of the complete arterial trees from proximal to distal vessels with adequate SNR. 16,25,27 Moreover, a hybrid of pCASL and PASL was suggested when using large FOV for imaging of extracranial carotid arteries, which could also minimize disappearance of the arterial signal due to fresh unlabeled blood flowing into the imaging volume. 41…”
Section: Labeling Module (General)mentioning
confidence: 99%